Nutritional supplements for weight gain - Clarkson, P. M. (1998)
1. Among the most popular nutritional supplements marketed to enhance muscle mass are chromium, creatine, vanadyl sulfate, boron, beta-hydroxy-beta-methyl butyrate (HMB), protein powders, and amino acids.